Orthognathıc Surgery İn A Skeletal Class Iıı Anterior Open-Bite Case. (A Case Report) (Galenos Yayinevi, 1998)
Anterior open-bite cases are considered functionally and aesthetically as a severe syndrome and especially treatment planning of skeletal anterior open-bite cases requires elaboreted diagnostic and therapeutic implications. Treatment of such dentofacial deformities mostly requires a combination of orthodontic and orthognatic surgery procedures. Application of such procedures help to achieve normal jaw function, optimal facial esthetics and long-term stability. In this paper the orthodontic treatment of a Class III anterior open-bite case in combination with ortognathic surgery is presented and the treatment approach is discussed.